3D printed hybrid scaffolds for bone regeneration using calcium methoxyethoxide as a calcium source - Heyraud, Agathe; Tallia, Francesca; Sory, David; Ting, Hung-Kai; Tchorzewska, Anna; Liu, Jingwen; Pilsworth, Hannah L.; Lee, Peter D.; Hanna, John V.; Rankin, Sara M.; Jones, Julian R. (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Hybrids consist of inorganic and organic co-networks that are indistinguishable above the nanoscale, which can lead to unprecedented combinations of properties, such as high toughness and controlled degradation. Methods: We present 3D printed bioactive hybrid scaffolds for bone regeneration, produced by incorporating calcium into our “Bouncy Bioglass”, using calcium methoxyethoxide (CME) as the calcium precursor. SiO2-CaOCME/PTHF/PCL-diCOOH hybrid “inks” for additive manufacturing (Direct Ink Writing) were optimised for synergy of mechanical properties and open interconnected pore channels. Results and Discussion: Adding calcium improved printability. Changing calcium content (5, 10, 20, 30, and 40 mol.%) of the SiO2-CaOCME/PTHF/PCL-diCOOH hybrids affected printability and mechanical properties of the lattice-like scaffolds. Hybrids containing 30 mol.% calcium in the inorganic network (70S30CCME-CL) printed with 500 µm channels and 100 µm strut size achieved the highest strength (0.90 ± 0.23 MPa) and modulus of toughness (0.22 ± 0.04 MPa). These values were higher than Ca-free SiO2/PTHF/PCL-diCOOH hybrids (0.36 ± 0.14 MPa strength and 0.06 ± 0.01 MPa toughness modulus). Over a period of 90 days of immersion in simulated body fluid (SBF), the 70S30CCME-CL hybrids also kept a stable strain to failure (~30 %) and formed hydroxycarbonate apatite within three days. The extracts released by the 70S30CCME-CL hybrids in growth medium did not cause cytotoxic effects on human bone marrow stromal cells over 24 h of culture.